القيود الواردة على إجراءات التعاقد بأسلوب المناقصة العامة - العاني, وسام صبار; حامد, ابتسام (Journal of Legal Sciences, 2019)
In the domain of public law administration enjoys the privileges of public power, but it is in the field of administrative contracts is not free contract in any way you want, Valmushara intervenes to restrict the freedom of administration to follow a contracting methods set forth in, the most important of these methods is the public tender method, as a general principle of the contract, so Leaders are subject to a number of legal restrictions in the conclusion of their contracts do not meet like individuals in the conclusion of their contracts own, because they do not equated with individuals to freedom of expression of will to conclude contracts, and justification that the administration in its contract aims to achieve the public interest, and they behave in public money is in the budget General state ,, so tightened restrictions on freedom of administration when its contract in order to achieve two main goals: first to achieve the biggest Save as much financial as possible through the selection of management of the contractor who offers the best tender in terms of financial and technical conditions, and the second goal to enable management to choose the contractor to stop and most capable technical the implementation of the project, which administration is keen to achieve.The legislator has imposed restrictions on the freedom of administration are formalities before and during the conclusion of the contract, and most of the legislation is keen to organize these restrictions in order to prevent abuses and unfair competition, which prompted this legislation in the field of administrative contracts to regulate contracting methods and the most important public tender, in order to ensure the achievement of the basic principles governed by the principle of openness and freedom of competition, equality and equal opportunities, which would broaden the circle of competition by creating real guarantees a source of contentment bidding and trust providers in the trading department.